Pengaruh Pendapatan Per Kapita Dan Kontribusi Sektor Jasa Terhadap Penerimaan Pajak Di Negara Berpendapatan Tinggi Di Asia Timur Dan Pasifik Dengan Kualitas Peraturan Sebagai Pemoderasi - Prabowo, Dhinnessa; Wijaya, Suparna (PT Wim Solusi Prima, 2023)
Tax is a state financial instrument imposed by the government. Taxes are collected to then finance state programs and activities. The role of taxes is very important for the development of a country. This study aims to analyze the influence exerted by per capita income, share of service in GDP, with Regulatory Quality as a moderator on tax revenues, especially those that occurred in high-income Asia Pacific countries in 2002-2019. The technique that the authors use is the analysis of panel data regression data that has been treated and selected the best model, namely the Feasible Generalized Least Squares (FGLS). The test results show that all variables simultaneously affect tax revenue. Partially, the share of service has a negative and significant effect while per capita income and the quality of regulations have no effect on tax revenues. Regulatory quality weakens the relationship between per capita income and tax revenues while not moderating the relationship between share of service in GDP and tax revenues. Based on the results of this study, the recommendation from the results of this study is that policies are needed that can maximize the service sector for acceptance and improve the quality of regulations on per capita income.